ECONOMIC ESSENCE OF FINANCIAL REPORTING AND SIGNIFICANCE OF COMPOSING IT IN ACCORDANCE WITH THE REQUIREMENTS ON INTERNATIONAL STANDARDS - F. Ochilov; E. Ollayorov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Nowadays, new, modern approaches to the issues of evaluating the results of financial and economic activity of economic entities reflected in financial statements are very necessary. This requires conducting in-depth studies on the existing theoretical, organizational and legal bases and practical problems of improving the quality of audit activity, as well as organizing and developing external and internal audit inspections at a modern level in our republic. On the one hand, a systematic approach to the international experiences of auditing activities, their in-depth analysis, and on the other hand, making maximum use of our knowledge about the features of the Uzbek model of market economy recognized in the world community, it is clear that there is a need for the prospective development of a special organizational form of control for users of financial reporting information in the conditions of economic liberalization.